Maxim Violations and Humor in Trevor Noah’s Stand-Up Comedy: A Pragmatic Analysis - Pratama, Joseph Colin Impian; Ayomi, Putu Nur; Lumabas, Baby Lyn Aquino (Journal of Language and Literature Studies, 2025)
This study aims to analyze the violation of conversational maxims in Trevor Noah’s stand-up comedy performance entitled “How to Not Order at an Indian Restaurant”. This study uses a qualitative descriptive method with Grice’s Principle of Cooperation theory as the main analytical framework. Data in the form of video transcripts were analyzed to identify the types of maxim violations that occur, as well as to understand how these violations function in building humorous effects. The results showed that all four types of maxims-quantity, quality, relevance, and manner-were violated in the performance, with the violation of the maxim of relevance being the most dominant. The findings show that maxim violations do not necessarily hinder communication, but can be creatively used to create humor and convey cultural messages implicitly to the audience. This study contributes to the broader field of pragmatics by demonstrating how non-cooperative language use can enhance audience engagement and meaning-making. It also advances humor theory by highlighting the pragmatic mechanisms through which linguistic deviation fosters comedic effect and cross-cultural understanding.